2020
DOI: 10.35542/osf.io/dmu4c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the Design of Microlearning for Korean Adult Learners

Abstract: Considering the increasing demand for microlearning in informal learning spaces, the main purpose of this research is to examine the design of microlearning perceived by adult learners and experts in Korea. The research questions include: (1) what modality and content length do adult learners perceive to be relevant for microlearning? (2) what content areas do adult learners perceive to be relevant for microlearning? and (3) what are the expected impacts and future directions of microlearning perceived by the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Informal learning environments that enable self-directed learning are gaining prominence beyond traditional structured learning methods. In these informal learning settings, individuals voluntarily engage in a learning environment based on their interests and needs (So et al, 2018). The microlearning approach aligns with the fast-paced and task-focused learning and working models of today, making informal learning possible through small, socially interactive steps and micro content units (Souza et al, 2015).…”
Section: Microlearning and Micro Contentsmentioning
confidence: 99%
“…Informal learning environments that enable self-directed learning are gaining prominence beyond traditional structured learning methods. In these informal learning settings, individuals voluntarily engage in a learning environment based on their interests and needs (So et al, 2018). The microlearning approach aligns with the fast-paced and task-focused learning and working models of today, making informal learning possible through small, socially interactive steps and micro content units (Souza et al, 2015).…”
Section: Microlearning and Micro Contentsmentioning
confidence: 99%
“…Both micro and macrolearning be conceptualised in many ways referring to different aspects, which in turn include different areas, as shown in Table 1 [17]. Recently, an interesting study which examines the design of microlearning showed that adult learners have contrasting opinions about the content areas perceived to be relevant for macrolearning, conceived as longer timeframe, and microlearning [18]. Adult learners who need to keep acquiring new information in order to keep up with fast societal changes, rely on microlearning as an effective approach for obtaining that information, whereas macrolearning was seen as more appropriate for deepening knowledge.…”
Section: Microlearning Ubiquitous and Adult Learning Contextsmentioning
confidence: 99%
“…The authors suggest that institutions that intend to develop microlearning should consider the dual structure of content delivery, so that learners who want to keep up with topical content can study microcontents while those who prefer to deepen their knowledge on more stabilised areas can attend e-learning courses. However, it should be noted that whether microlearning content delivers merely information rather than knowledge is a matter of debate and further research is needed on the best ways to help learners to progress from the information consumption stage to the knowledge building stage [18].…”
Section: Microlearning Ubiquitous and Adult Learning Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microlearning is an instructional method that delivers concise learning content in easily digestible formats, addressing the limitations of traditional training approaches (Hug, 2022). It allows learners to acquire knowledge in short bursts, aligning with their fast-paced lifestyles (So et al, 2020). Microlearning can take diverse forms, such as videos, quizzes and simulations, accessible through various devices (Ghirardini, 2011).…”
Section: Introductionmentioning
confidence: 99%